Perencanaan Unit Produksi Air Minum Kecamatan Bangko Pusako, Rimba Melintang Dan Tanah Putih Tanjung Melawan, Kabupaten Rokan Hilir - M Caesar Grendi; Jecky Asmura; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Fulfillment of drinking water needs in Bangko Pusako, Rimba Melintang and Tanah Melawan Subdistricts in Rokan Hilir Regency still relies from bottled water, boreholes, plumbing, river water and springs and rainwater, where the quality and quantity of these sources are not guaranteed. In 2016 drinking water needs amounted to 226 liters / second and will reach 312.5 liters / second in 2036, so that it is necessary to plan the installation of a drinking water production unit that can meet the drinking water needs of the region for the next 20 years with raw water coming from the Rokan River. Based on mass balance analysis, units obtained that are able to process raw water with quality according to PERMENKES number 492 in 2010. The planned processing units are intake, pre-sedimentation, coagulation, flocculation, sedimentation, filtration, disinfection and neutralization.Keywords: Rokan Hilir, Production Unit, Water requirements, Water Treatment, Rokan River